What drives the vaccination intention against COVID-19? Application of EPPM, TAM, and theories of risk assessment - Zhenjing Pang; Xinlin Ma (Taylor & Francis Group, 2023)
Vaccines are widely used to fight against COVID-19. However, COVID-19 vaccine hesitancy appears as some individuals are concerned with COVID-19 vaccines. This study investigates the vaccination intention against COVID-19 in China with the Extended Parallel Process Model (EPPM), Technology Acceptance Model (TAM), and theories of risk information assessment. Results showed that the formation mechanism of vaccination intention could be considered a psychological process, as subjective knowledge was a primary influence on correspondents' weighting of both the potentially positive (usefulness) and negative effects (threat) of vaccination. This unequal consideration then resulted in different levels of fear arousal between subjects. Driven by usefulness/threat perception and fear, people conducted different decision strategies, so-called analytical assessment, and experiential assessment to make vaccination decision. In addition to the direct effects of experiential assessment on vaccination intention, two decision strategies and fear arousal also affected people's vaccination intention through the mediation role of vaccination attitude. For policymakers and stakeholders, this study provides a knowledge base for confidence-building, and emotional guidance concerning against COVID-19 vaccination.